Neomycin inhibits Megalocytivirus infection in fish by antagonizing the increase of intracellular reduced glutathione. Issue 127 (August 2022) - Deng, Hengwei; Li, Yeyu; Li, Jinling; Shen, Wenjie; Chen, Qiankang; Weng, Shaoping; He, Jianguo; Xu, Xiaopeng
Abstract: Infectious spleen and kidney necrosis virus (ISKNV) is the type species of the Megalocytivirus genus that infects a number of marine and freshwater fishes, causing huge economic losses in aquaculture. The ISKNV infection leads to increase of reducing power in cells. As the antibiotic neomycin can promote the production of reactive oxygen species (ROS) in animal cells, in the current study, the potential therapeutic effect of neomycin on ISKNV infection was explored. We showed that neomycin could decrease the reducing power in cultured MFF-1 cells and inhibit ISKNV infection by antagonizing the shift of the cellular redox balance toward reduction. In vivo experiments further demonstrated that neomycin treatment significantly suppresses ISKNV infection in mandarin fish. Expression of the major capsid protein (MCP) and the proportion of infected cells in tissues were down-regulated after neomycin treatment. Furthermore, neomycin showed complex effects on expression of a set of antiviral related genes of the host. Taking together, the current study suggested that the viral-induced redox imbalance in the infected cells could be used as a target for suppressing ISKNV infection. Neomycin can be potentially utilized for therapeutic treatment of Megalocytivirus diseases by antagonizing intracellular redox changes. Highlights: The improvement of reducing power in cells is important for Megalocytivirus replication. The anti- Megalocytivirus effect can be achieved by antagonizing intracellular redox imbalance. Neomycin inhibits ISKNV infection in vitro and in vivo. Immersion with neomycin increases survival rate of ISKNV-infected mandarin fish.